تأثير الأساليب القيادية على مستوى الأداء الوظيفي في شركات التأمين: دراسة تطبيقية على شركات التأمين بالأغواط - عاشور, عادل (جامعة الوادي - University of Eloued, 2017)
إن الكثير من المشكلات التي تواجه الإدارات عموما والمؤسسات المالية على وجه الخصوص ترجع إلى نقص المهارات القيادية اللازمة لتوجيه وترشيد الأداء الوظيفي للعاملين بهاته المؤسسات، ولذا فإن سبب ضعف وتدني الأداء الوظيفي للعاملين بالمؤسسات المالية ليس نقصا في قدراتهم و لكن النقص راجع بصفة أساسية إلى تخلف الإدارة والقيادة على وجه الخصوص كما ونوعا من خلال تأثرها بجوانب العملية القيادية (الرئيس، المرؤوس، الموقف)، فالقيادة الفعالة المتمثلة في القادة القائمين على العمل تكون قادرة على الوصول إلى توجيه القدرات والجهود بالصفة اللازمة؛ ومن هنا تتبين لنا العلاقة بين القيادة من خلال أساليبها المنتهجة من طرف القادة على حسب الموقف وهذا ما ينعكس على تحديد طبيعة مستوى الأداء الوظيفي للعاملين. وهكذا تكون القيادة قد استمدت أهميتها من قدرتها على الاستغلال الأمثل لمقومات الإدارة ومواردها في رفع الأداء وذلك من خلال انتهاج أساليب قيادية تتسم بالفعالية وتتلاءم مع الظروف الفعلية للعمل الإداري لأنه ليس هناك أسلوب قيادي محدد يتميز بالمثالية فهو دائما يرجع إلى طبيعة الموقف وبالتالي فدراستنا قد عمدت إلى الكشف عن الأساليب أو الأنماط القيادية المنتهجة في شركات التأمين ومدى تأثيرها على مستوى الأداء الوظيفي Many problems that face administrations in general and financial institutions in particular due to the lack of leadership skills necessary to guide and rationalize the functional performance of the employees of the institutions, therefore, the reason for the weak and low performance of the employees of financial institutions is not lack of capacity, but the deficiency that is mainly due to the failure of management and leadership in particular in terms of quantity and quality through the impact on aspects of the leadership process (President, subordinate, position) The effective leadership of the working leaders is capable of reaching the necessary capacities and efforts; hence the relationship between the leadership through the methods adopted by the leaders according to the situation and this is reflected in determining the nature of the level of performance of the employees. Thus, the leadership has derived its importance from its ability to make optimal use of the elements of management and its resources in raising performance through the adoption of leadership methods that are effective and appropriate to the actual conditions of administrative work because there is no specific leadership style characterized by idealism is always due to the nature of the situation and therefore, our study has revealed the methods or patterns of leadership used in insurance companies and their impact on the level of performance.
Effect of leadership methods on the level of performance in insurance companies
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: الأداء الوظيفي، الأساليب القيادية، القائد، المرؤوس; Functionality - Leadership styles - Leader - subordinate